Growth and Essential Carotenoid Micronutrients in Lemna gibba as a Function of Growth Light Intensity - Stewart, Jared J.; Adams, William W.; Escobar, Christine M.; López-Pozo, Marina; Demmig-Adams, Barbara (Frontiers in Plant Science, 2020)
Duckweed is a promising food crop with multiple benefits for space applications. Fresh duckweed could deliver synergistically acting essential antioxidant nutrients to a crew – but only if growth conditions provide the plant with the right cues to trigger antioxidant formation. We grew Lemna gibba under continuous growth light ranging from low to very high intensities (photosynthetic photon flux densities = PPFDs) in order to investigate the effect on plant growth, photosynthesis, and level of carotenoid antioxidants that are essential human micronutrients. Lemna gibba achieved remarkably high growth rates under modest growth PPFD by virtue of superior light absorption resulting from minimal self-shading and high chlorophyll levels. Conversely, L. gibba’s growth rate remained high even under very high growth PPFDs. This notable ability of L. gibba to avoid inactivation of photosynthesis and diminished growth under very high growth PPFDs resulted from a combination of downregulation of chlorophyll synthesis and increased biochemical photoprotection that limited a build-up of excessive excitation energy. This biochemical photoprotection included accumulation of zeaxanthin (an essential human micronutrient) and high levels of zeaxanthin-catalyzed thermal energy dissipation of excess excitation. Compared to the light levels needed to saturate L. gibba photosynthesis and growth, higher light levels were thus required for strong induction of the essential antioxidant zeaxanthin. These results indicate a need for design of light protocols that achieve simultaneous optimization of plant yield, nutritional quality, and light-use efficiency to circumvent the fact that the light requirement to saturate plant growth is lower than that for production of high zeaxanthin levels. How this trade-off between light-use efficiency of growth and nutritional quality might be minimized or circumvented to co-optimize all desired features is discussed.